Workforce globalisation, language and discourse: Recruitment of foreign nurses in the UK. (17th October 2022) - Kuznetsov, Andrei; Kuznetsova, Olga; Fernández de Simón de la Cruz, Jaime
Abstract : The globalisation of the labour market creates new challenges for organisations when hiring. This article addresses one such challenge that is rarely in the spotlight: the implications of the choice of a language proficiency test for non-native speakers by the hiring organisation. We use the UK National Health Service (NHS) recruitment practices as an example. With the help of a staged experiment, this practice-based study argues that the current international recruitment procedure to the NHS tends to underestimate some important differences between language as a formalised system of words and grammatical rules and discourse as 'language in action', causing the loss of staffing capacity. It follows from our analysis that when setting the requirements and objectives of a language test, the recruiting organisations need to consider more explicitly the social and cultural context in which their employees operate and the impact of this context on the communication demands faced by the staff.